Modernization of Creative Competence of Students in Medical Higher Educational Institutions - Munira Rasulovna, Kadirova; Shahlo Pulatovna, Ergasheva (International Journal of Psychosocial Rehabilitation, 2020)
This article was written with the aim of theoretically substantiate, develop and, in the course of experimental research, test the methodology for modernizing the creativity of students in medical higher educational institutions. The following tasks are solved in the article as: to clarify the main aspects and components of students’ creative activity based on a comparison of the concepts of creativity and creativity, modernization of the classification of creative abilities for teaching students; to determine the motivation, nature, structure, characteristics and pedagogical conditions of increasing the creative activity of students in the process of teaching English in a medical university; to determine the system of levels, content and factors of students’ creative activity, improving the methodology with the criteria selected in the study of the English language; to evaluate the effectiveness of the application of the model for enhancing and modernizing the creative activities of students in the process of teaching English in medical schools. Based on the problem, a training methodology was developed, didactic foundations were determined and conclusions were drawn